Apatinib, a novel tyrosine kinase inhibitor, suppresses tumor growth in cervical cancer and synergizes with Paclitaxel. Issue 10 (19th May 2018) - Qiu, Haifeng; Li, Jing; Liu, Qiuli; Tang, Mei; Wang, Yuan
ABSTRACT: Apatinib is a novel tyrosine kinase inhibitor that targets VEGFR2 signal and exhibits potent anti-tumor effects in human cancers. In this study, we aim to investigate the efficacy of Apatinib in cervical cancer. The protein expression of VEGFR2 and its relationships with clinical parameters were investigated in a panel of cervical cancer patients. In vitro, a series of experiments were performed to detect the effects of Apatinib on the proliferation, apoptosis and cell cycle in cervical cancer cells. Both the immortalized cell lines and primary cultured tissues were used to investigate the synergy between Apatinib and chemotherapeutic drugs. The in vivo effects of Apatinib were validated in a nude mouse model. Compared to that in normal cervix, VEGFR2 protein was significantly upregulated in cervical cancer tissues (P < 0.001); this was positively correlated with advanced tumor stage, lymph node metastasis, and a poor prognosis. In vitro, Apatinib markedly induced apoptosis and G1-phase arrest, suppressed cell growth, and decreased colony formation ability. We also found that primary cancer tissues with higher level of VEGFR2 were much more sensitive to Apatinib. Further, we proved that Apatinib significantly increased the sensitivity to Paclitaxel in cervical cancer cells and the mouse model. Collectively, we firstly report the anti-tumor efficacy of Apatinib in cervical cancer. Moreover, Apatinib synergized with Paclitaxel to achieve more significant suppression on tumor growth, proposing that Apatinib might be a potent drug for cervical cancer.